2017
DOI: 10.3389/fimmu.2017.00005
|View full text |Cite
|
Sign up to set email alerts
|

Indian Long-term Non-Progressors Show Broad ADCC Responses with Preferential Recognition of V3 Region of Envelope and a Region from Tat Protein

Abstract: HIV-specific antibody-dependent cell cytotoxicity (ADCC) is likely to be important in governing protection from human immunodeficiency virus (HIV) and slowing disease progression. Little is known about the ADCC responses to HIV-1 subtype C. We characterized ADCC responses in HIV-1 subtype C-infected Indian subjects with slow disease progression and identified the dominant antigenic regions recognized by these antibodies. ADCC responses were measured in plasma from 34 long-term non-progressors (LTNPs), who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Thus, the ADCC antibody at the non-early phase would not be able to respond to these original V3 epitopes as we previously reported on ADCC epitopes of HIV-1 in asymptomatic infected individuals. 12 Our finding of peptide 85 (aa 336-350: GTKWNEVLKKVTKKL) as dominant ADCC epitope was also correspondent to the data of Kulkarni et al 15 They demonstrated the recognition of novel antigenic ADCC epitope in sera of LTNPs at the C3 region (aa 331-360: CNISEEKWNKTLQRVSEKLKEHFPNKTIKF).…”
Section: Common Adcc Epitopes Of Hiv-1 Crf01_aesupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the ADCC antibody at the non-early phase would not be able to respond to these original V3 epitopes as we previously reported on ADCC epitopes of HIV-1 in asymptomatic infected individuals. 12 Our finding of peptide 85 (aa 336-350: GTKWNEVLKKVTKKL) as dominant ADCC epitope was also correspondent to the data of Kulkarni et al 15 They demonstrated the recognition of novel antigenic ADCC epitope in sera of LTNPs at the C3 region (aa 331-360: CNISEEKWNKTLQRVSEKLKEHFPNKTIKF).…”
Section: Common Adcc Epitopes Of Hiv-1 Crf01_aesupporting
confidence: 89%
“…15 They proposed the potential role of this anti-V3 ADCC response in viral control which may contribute to the slower disease progressors. Their epitope sequences included our full epitope peptide 78 (aa 308-322: SINIGPGQVFYRTGD) and partial of epitope peptide 71 (aa 290-294:…LNKSV).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ECs and LTNPs appear to have enhanced ADCC response and target both the viral Env and regulatory/accessory viral proteins, such as Vpu, that are not observed in progressors [ 66 •]. Moreover, ADCC activity against the structural Env V3 loop region as well as against Gag and Tat proteins is disproportionately higher in controllers [ 78 , 79 ]. Importantly, although abundant, ADCC is not the only innate effector function induced at high levels in controllers.…”
Section: Correlates Of Spontaneous Hiv Controlmentioning
confidence: 99%
“…As opposed to ADNKA, ADCC measures target cell phenomena arising from the bridging of effector and target cells by an Ab whose Fc portion binds CD16 on effector cells and whose Fab portion recognizes an antigen on target cells. In the context of ADCC function-directed HIV Env gp120-coated target cells, the target antigens recognized by ADCC competent Abs are HIV Env ( 30 , 78 , 100 ). ADCC activity directed to HIV infected may also recognize Tat ( 100 ).…”
Section: Measuring Adcc Activitymentioning
confidence: 99%
“…In the context of ADCC function-directed HIV Env gp120-coated target cells, the target antigens recognized by ADCC competent Abs are HIV Env ( 30 , 78 , 100 ). ADCC activity directed to HIV infected may also recognize Tat ( 100 ).…”
Section: Measuring Adcc Activitymentioning
confidence: 99%